Socio emotional wealth preservation in the REIT industry: An exploratory study - Magdy Noguera; Erick P. C. Chang (International Journal of Financial Studies, 2014)
Our study uses the Socio Emotional Wealth Perspective (SEW) to test our contention that Real Estate Investment Trust (REIT) founders are more inclined to satisfy first their non-economic goals rather than satisfying the economic goals of REIT shareholders. We test our hypotheses with an unbalanced panel dataset that includes an average of 66 publicly-traded equity REITs from 1999 - 2012 that produced 921 REIT-year observations. Our exploratory results provide evidence of SEW preservation as REITs led by founders' successors tend to underperform; however, the family identification with the REIT affects performance positively. This is one of the first studies that merge the REIT and the family business streams of research. Future directions are suggested.
Keywords: G29; G38; 330; REIT; socio emotional wealth; succession; family identification